The Economics of Sustainability : Causes and Consequences of Energy Market Transformation - Arezki, Rabah (World Bank, Washington, DC, 2019)
The paper deals with the economics of sustainability associated with the transformation of energy markets. It emphasizes the interrelations between technical changes and energy markets and how in turn the resulting transformations alter the sustainability of economic systems that are dependent on these markets. It also explores how innovation (or the lack thereof) is intimately linked to the ability of energy rich economies to adapt and transform. The agenda is especially relevant for oil rich countries that have announced or already put in place policies to help transform their economies and move away from dependence on oil. The agenda is also relevant for the global community, as it relates to the economic consequences of the needed transformation of energy markets to support the goal of limiting global warming by reducing greenhouse gas emissions.